The bioelectricity of plant–biotic interactions - Moratto,E; Sena,G (Bioelectricity, 2023)
Plants form mutually beneficial or antagonistic interactions with organisms from various kingdoms of life. A clear understanding of the underlying mechanisms is fundamental for crop protection and environmental preservation. Although historically overlooked, the role of plant bioelectricity in initiating and maintaining biotic interactions is recently emerging as an exciting research topic. In this review, we summarize the state-of-the-art regarding the role of plant bioelectricity in biotic interactions focusing on both shoots and roots. We describe how root bioelectricity mediates interactions with pathogens and symbionts from different phyla, and the role played by flower electric fields in pollination.